Effect of larch wood extractive leaching on accelerated weathering aging durability of oil-based coatings - Dvořák Ondřej; Kvietková Monika Sarvašová; Horák Petr; Kubista Kryštof; Pánek Miloš; Štěrbová Irena (Central European Forestry Journal, 2023)
Wood is a natural material and is subject to degradation due to weather, UV radiation, and humidity. Wood is composed of many components. The basic structural elements of wood include cellulose, hemicellulose, and lignin. Furthermore, these are accompanying substances, which also include extractive substances. Specifically, these substances, together with lignin, have a negative effect on its life thanks to their chemical reactions, which are initiated mainly by UV radiation (so-called photodegradation). This study evaluates the effect of controlled degradation of extractives and lignin on the surface of the wood before the application of the coating system and also on its overall service life. Samples of larch wood (Larix decidua Mill.) were exposed to exterior natural influences in Prague (Czech Republic) according to EN 927–3 (2020) for 10 and 20 weeks. Subsequently, the samples were sterilized in an autoclave, due to possible contamination of the surface with fungi. The specimens were then treated with two oil–coating systems (V–420 and V–429). Subsequently, they were exposed to artificial aging in a UV chamber according to EN 927–6 (2019). Testing occurred at predetermined time intervals of 0, 1, 3, and 6 weeks, roughly corresponding to 0, 2, 6, and 12 months outdoors. The evaluated factors were the change in color, gloss, and surface wettability. The results showed a slightly positive effect of surface washout lasting ten weeks before applying the coating system.